## Chapter 10.5

## Q. 10.5.2

## Q. 10.5.2

** Using the Binomial Theorem**

Expand: (x+2)^4.

## Step-by-Step

## Verified Solution

We use the Binomial Theorem

(a+b)^n=\left(\begin{array}{l}n \\0\end{array}\right) a^n+\left(\begin{array}{l}n \\1\end{array}\right) a^{n-1} b+\left(\begin{array}{l}n \\2\end{array}\right) a^{n-2} b^2+\left(\begin{array}{l}n \\3\end{array}\right) a^{n-3} b^3+\cdots+\left(\begin{array}{l}n \\n\end{array}\right) b^n

to expand (x+2)^4. In (x+2)^4, a = x, b = 2, and n = 4. In the expansion, powers of x are in descending order, starting with x^4. Powers of 2 are in ascending order, starting with 2^0. (Because 2^0 = 1, a 2 is not shown in the first term.) The sum of the exponents on x and 2 in each term is equal to 4 , the exponent in the expression (x+2)^4.

=x^4+8 x^3+24 x^2+32 x+16